Early Nasojejunal Nutrition Versus Early Oral Feeding in Patients After Pancreaticoduodenectomy: A Randomized Controlled Trial - Liu, Xinchun; Chen, Qiuyang; Fu, Yue; Lu, Zipeng; Chen, Jianmin; Guo, Feng; Li, Qiang; Wu, Junli; Gao, Wentao; Jiang, Kuirong; Dai, Cuncai; Miao, Yi; et al. (Frontiers in Oncology, 2021)
Objective The aim of this study was to test the hypothesis that early oral feeding (EOF) is superior to early nasojejunal nutrition (ENN) after pylorus-preserving pancreaticoduodenectomy (PPPD) in terms of delayed gastric emptying (DGE). Background DGE is a common complication after PPPD. Although EOF after PPPD is recommended by several international guidelines, there is no randomized trial to support this recommendation. Methods From September 2016 to December 2017, a total of 120 patients undergoing PPPD were randomized into the ENN, EOF, or saline groups at a 1:1:1 ratio (40 patients in each group). The primary endpoint was the rate of clinically relevant DGE. Secondary endpoints included overall morbidity, postoperative pancreatic fistula, post-pancreatectomy hemorrhage, abdominal infection, length of hospital stay, reoperation rate, and in-hospital mortality. Results The baseline characteristics and operative parameters were comparable between the groups. The incidence of clinically relevant DGE varied significantly among the three groups (ENN, 17.5%; EOF, 10.0%; saline, 32.5%; p =0.038). The saline group had a higher clinically relevant DGE rate than the EOF group (p = 0.014). The saline group also had greater overall morbidities than the ENN and EOF groups (p = 0.041 and p = 0.006, respectively). There were no significant differences in other surgical complication rates or postoperative hospital stay. No mortality was observed in any of the groups. Conclusions Nutritional support methods were not related to DGE after PPPD. EOF was feasible and safe after PPPD, and additional ENN should not be routinely administered to patients after PPPD. Clinical Trial Registration ClinicalTrials.gov, identifier NCT03150615.